Recoloring Algorithms for Colorblind People: A Survey - Ribeiro, Madalena (2020)
Color is a powerful communication component, not only as part of the message meaning but also as a way of discriminating contents therein. However, 5% of the world’s population suffers from color vision deficiency (CVD), commonly known as colorblindness. This handicap adulterates the way the color is perceived, compromising the reading and understanding of the message contents. This issue becomes even more pertinent due to the increasing availability of multimedia contents in computational environments (e.g., web browsers). Aware of this problem, a significant number of CVD research works came up in the literature in the past two decades to improve color perception in text documents, still images, video, and so forth. This survey mainly addresses recoloring algorithms toward still images for colorblind people, including the current trends in the field of color adaptation.